The Effect of Isotonic Drinks on the Body's Recovery Time After Performing the Harvard Step Test - Firman Erdona Sebayang; Refi Ikhtiari; Ahmad Raif (CV. Inara, 2022)
Sport is an activity that is mostly done in the world. One of the most common problems experienced when exercising is dehydration. Dehydration occurs due to the amount of mineral fluid that is lost / out of the body so that it can cause the body to experience fatigue. During exercise or high physical activity, it has the potential to increase the pulse frequency because the higher the physical activity, the higher the increase in blood flow to supply nutrients and oxygen. The body will experience fatigue as a sign that the body has reached the limit of activity so that the body must rest. When the body rests the body will undergo a recovery process. At the time of recovery, hydration is needed to replace the body's lost minerals. While isotonic drinks have a composition similar to lost body fluids than ordinary mineral water. To determine the effect of isotonic fluid on blood pressure after doing the Harvard Step Test on recovery time, knowing the effect of isotonic fluid on pulse rate after doing the Harvard Step Test on recovery time, knowing the effect of isotonic fluid on Respiration rate after doing the Harvard Step Test on recovery time. The sig-p value of the normality test of recovery time. Respiration rate, heart rate and blood pressure with Shapiro Wilk were 0.001, 0.000 and 0.021 and 0.041, respectively, all of which were smaller than 0.05. The average value of the recovery time for the Respiratory Rate pre-test was 21.93 minutes while the average value for the recovery time for the Respiratory Rate post-test was 9.07 minutes with a sig-p value = 0.000 (p<0.05). This means that there is a significant decrease in the recovery time of the respiratory rate after administration of isotonic fluids (p = 0.000 < 0.05). The mean (average) recovery time of the pre-test Heart Rate is 21.80 minutes while the average value of the post-test Heart Rate recovery time is 9.20 minutes with a sig-p value = 0.000 (p<0.05). This means that there is a significant decrease in the recovery time of the Heart Rate after administration of isotonic fluids (p = 0.000 < 0.05). The average value of recovery time for pre-test blood pressure was 21.20 minutes while the average value of recovery time for post-test blood pressure was 9.80 minutes with sig-p = 0.000 (p<0.05). This means that there is a significant decrease in blood pressure recovery time after administration of isotonic fluids (p = 0.000 < 0.05). The average value of the recovery time for the respiratory rate pre-test was 21.03 minutes while the average value for recovery time for the respiratory rate post-test was 9.97 minutes with a sig-p value = 0.000 (p<0.05). This means that there is a significant decrease in the recovery time of the Respiration Rate after giving mineral water (p = 0.000 < 0.05). The average pre-test heart rate recovery time was 21.70 minutes while the post-test heart rate recovery time average was 10.30 minutes with sig-p = 0.000 (p<0.05). This means that there is a significant decrease in the recovery time of the Heart rate after giving mineral water (p = 0.000 < 0.05). The average value of recovery time for pre-test blood pressure was 16.27 minutes while the average value of post-test BP recovery time was 14.73 minutes with sig-p value = 0.653 (p>0.05). This means that there is no significant decrease in blood pressure recovery time after administration of mineral water (p = 0.000 < 0.05). The average value of isotonic recovery time is 36.68 minutes while the average value of mineral water recovery time is 54.32 minutes with a sig-p value = 0.001 (p<0.05).